Vermächtnis: nachgelassene Schriften - Fürtwängler, Wilhelm 1886-1954 (Wiesbaden Brockhaus, 1975)
For more than three decades, the name Furtwängler has become a byword for musical experience in the musical consciousness of the whole world. When Furtwängler took up the baton or the pen, he always had something important to say and did so with clear determination. Furtwängler lived in the music, and therefore music, whether classical or modern, was something absolutely alive to him. With these words, the Luzerner Tagblatt characterised the master's personality and character. His estate contained notes, drafts and essays, the most beautiful of which are presented in this volume. His broad, deep view encompassed music, art in general, contemporary events, people and everything human. His observations thus reflect the intellectual life of the last 40 years far beyond the purely musical. (Translated with DeepL.com)
Keywords: Music philosophy and esthetics